A Smartphone Application Designed to Engage the Elderly in Home-Based Rehabilitation - Androutsou, Thelma; Kouris, Ioannis; Anastasiou, Athanasios; Pavlopoulos, Sotiris; Mostajeran, Fariba; Bamiou, Doris-Eva; Genna, Gregory J.; Costafreda, Sergi G.; Koutsouris, Dimitrios (Frontiers in Digital Health, 2020)
As life expectancy increases, it is imperative that the elderly take advantage of the benefits of technology to remain active and independent. Mobile health applications are widely used nowadays as they promote a healthy lifestyle and self-management of diseases, opening new horizons in the interactive health service delivery. However, adapting these applications to the needs and requirements of the elderly is still a challenge. This article presents a smartphone application that is part of a multifactorial intervention to support older people with balance disorders. The application aims to enable users to self-evaluate their activity and progress, to communicate with each other and, through strategically selected motivational features, to engage with the system with undiminished interest for a long period of time. Mock-up interfaces were evaluated in semi-structured focus groups and interviews that were performed across three European countries. Further evaluation in the form of four pilot studies with 160 participants will be performed and qualitative and quantitative measures will be used to process the feedback about the use of the application.